Patterns of tobacco consumption among residents of a rural settlement: a cross-sectional study - Andrécia Cósmem da Silva; Lorena Silva Vargas; Roselma Lucchese; Bruno de Souza Calixto; Rafael Alves Guimarães; Ivania Vera; Paulo Alexandre de Castro; Valéria Pagotto; Inaina Lara Fernandes (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Investigate patterns and factors associated with tobacco consumption among residents of a rural settlement. METHODS A cross-sectional study conducted between September and November 2014, with 172 residents of a rural settlement in the Midwest region of Brazil. We analyzed as dependent variables tobacco consumption at some point in life; current tobacco consumption; tobacco abuse; and the high risk of nicotine dependence, with sociodemographic variables associated with tobacco use, and we applied the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) and Self-Reporting Questionnaire (SRQ-20). RESULTS The prevalence of tobacco use in life, current use, tobacco abuse, and high risk of nicotine dependence were 62.2%, 20.9%, 59.8%, and 10.3%, respectively. Advanced age, low education level, evangelical religion, marijuana use, hypnotic or sedative consumption, and male gender were factors associated with smoking patterns in the settlers. CONCLUSIONS There was a high prevalence of smoking patterns, evidencing the need for public policies on tobacco prevention and control in this population.